Photodynamic inactivation of Candida albicans and Candida tropicalis with aluminum phthalocyanine chloride nanoemulsion. Issue 5 (May 2020) - Rodrigues, Gabriela Braga; Brancini, Guilherme Thomaz Pereira; Pinto, Marcelo Rodrigues; Primo, Fernando Lucas; Wainwright, Mark; Tedesco, Antonio Claudio; Braga, Gilberto Úbida Leite
Abstract: The in vitro susceptibilities of Candida albicans and Candida tropicalis to Antimicrobial Photodynamic Treatment with aluminum phthalocyanine chloride in nanoemulsion (ClAlPc/NE) were investigated. PS concentration- and fluence-dependent cell survival after APDT were compared before and after unbound extracellular PS had been washed out. The PS uptake and its subcellular localization were also determined. Exposure to light in the absence of the PS and treatment with the PS in the absence of light did not kill the fungi. APDT with ClAlPc/NE resulted in a reduction of five orders of magnitude in viability for C. albicans and between four and five orders of magnitude for C. tropicalis . Washing the cells to remove unbound PS before light exposure did not impair fungal inactivation, suggesting that cell photosensitization was mainly carried out by cell bound ClAlPc. The degree of ClAlPc uptake was dependent on its concentration. Internalization of ClAlPc by C. albicans and C. tropicalis was confirmed by confocal fluorescence microscopy that showed the PS does not penetrate the nucleus and instead accumulates in specific regions of the cytoplasm. Our results show that incorporating the water-insoluble ClAlPc into a nanoemulsion leads to an efficient formulation capable of photoinactivating both Candida species.